Awareness, use and barriers to family planning services among female students at the National University of Lesotho, Roma, Lesotho - Akintade, Oluwasanmi Lawrence (University of Limpopo ( Medunsa Campus), 2010)
Background: Sexual health of young people is a matter of public health concern and Reproductive health occupies a central position in health and development. Unwanted pregnancy and sexually transmitted infections among young women can be prevented through effective use of contraception. Unmet need for contraception in developing world and rates of unintended pregnancy among young women is high. Aim of the Study: To assess the level of awareness of contraceptives and utilization of family planning services among young women and barriers that hinders effective use of such services Methods: A quantitative descriptive survey was conducted among 360 female undergraduate students of the National University of Lesotho, Roma, Lesotho. A hand delivered self administered questionnaire was used to collect data with the help of four trained research assistants. Epi info version 3.5 was used for data entry and analysis. Results: Awareness of family planning is high among the participant (98.3%); Condom is the most commonly known and used family planning method. Level of sexual experience and Contraceptive prevalence is high. Married status is associated with current use, positive perception on health benefit while Formal teaching on family planning is associated with misconceptions. Conclusion: The level of awareness and Utilization of family planning services is high among female students of university of Lesotho. Access to services is good but there are misconceptions. There is the need to introduce family planning teaching that is based on accurate knowledge to school curriculum
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Family planning; Family planning services